Withaferin A induces apoptosis in human melanoma cells through generation of reactive oxygen species and down-regulation of Bcl-2 - Mayola, E.; Gallerne, C.; Esposti, D.; Martel, C.; Pervaiz, Shazib; Larue, L.; Debuire, B.; Lemoine, A.; Brenner, C.; Lemaire, C. (Springer, 2011)
A high resistance and heterogeneous response to conventional anti-cancer chemotherapies characterize malignant cutaneous melanoma, the most aggressive and deadly form of skin cancer. Withaferin A (WFA), a withanolide derived from the medicinal plant Withania somnifera, has been reported for its anti-tumorigenic activity against various cancer cells. For the first time, we examined the death-inducing potential of WFA against a panel of four different human melanoma cells and investigated the cellular mechanisms involved. WFA induces apoptotic cell death with various IC50 ranging from 1.8 to 6.1 lM. The susceptibility of cells toward WFA-induced apoptosis correlated with low Bcl-2/Bax and Bcl-2/Bim ratios. In all cell lines, the apoptotic process triggered by WFA involves the mitochondrial pathway and was associated with Bcl-2 down regulation, Bax mitochondrial translocation, cytochrome c release into the cytosol, transmembrane potential (DWm) dissipation, caspase 9 and caspase 3 activation and DNA fragmentation. WFA cytotoxicity requires early reactive oxygen species (ROS) production and glutathione depletion, the inhibition of ROS increase by the antioxidant N-acetylcysteine resulting in complete suppression of mitochondrial and nuclear events. Altogether, these results support the therapeutic potential of WFA against human melanoma. © Springer Science+Business Media, LLC 2011.